This is how we end things eaudiobook A novel. - Jacobs, R.J (HighBridge Audio, 2023)
Riley Sager meets If We Were Villains in a compelling new psychological thriller by R. J. Jacobs, following a tight-knit group of graduate students studying the psychology of lying. When one of them is discovered dead after an experiment, everything the group thought they knew about deception crumbles . . . Campus is empty, a winter storm is blowing in, and someone is lurking in the shadows, waiting for their chance to kill again. Forest, North Carolina. Under the instruction of enigmatic Professor Joe Lyons, five graduate students are studying the tedious science behind the acts of lying. But discovering the secrets of deception isn't making any of the students more honest though. Instead, it's making it easier for them to guard their own secrets-and they all have something to hide. When a test goes awry and one of them is found dead, the students find themselves trapped by a snowstorm on an abandoned campus with a local detective on the case. As harbored secrets begin to break the surface, the graduates must find out who's lying, who isn't, and who may have been capable of committing murder. It turns out deception is even more dangerous than they thought . . .